2015
DOI: 10.1109/jsen.2014.2362679
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Electrolyte-Gated Ion-Selective Sensors Based on Carbon Nanotube Networks

Abstract: We demonstrate the ion-selective response of an electrolyte-gated carbon nanotube network based field-effect transistor fabricated on a flexible polyimide substrate. Selective response towards the two prominent second messengers for cellcell communication, namely K + and Ca 2+ is demonstrated by modifying the carbon nanotube network with different polymeric ion-selective membranes. The sensing mechanism relies on the transduction of the ionic signal in an electrical one due to an ionactivity dependent change o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 39 publications
0
31
0
Order By: Relevance
“…In ISFETs, the sensing layer can either form the conducting channel (resistance‐modulated sensor) or the gate (capacitance‐modulated sensor). Flexible resistance‐modulated ISFETs using carbon nanotubes and a nanostructured oxide film (ZnO nanowall) as the channel sensing layer have been realized. In the study by Maiolo et al, a Nernstian response was observed.…”
Section: Flexible Ph Sensors and Ion Sensorsmentioning
confidence: 99%
“…In ISFETs, the sensing layer can either form the conducting channel (resistance‐modulated sensor) or the gate (capacitance‐modulated sensor). Flexible resistance‐modulated ISFETs using carbon nanotubes and a nanostructured oxide film (ZnO nanowall) as the channel sensing layer have been realized. In the study by Maiolo et al, a Nernstian response was observed.…”
Section: Flexible Ph Sensors and Ion Sensorsmentioning
confidence: 99%
“…Both single‐ and multi‐walled carbon nanotubes reached significant scientific attention as highly promising material for various applications, including electronics, optoelectronics, catalysis. Also different types of electrochemical sensors 15, benefit from applications of CNTs, including among others field effect transistors 14, 6, 7, 8, amperometric type devices/sensors [e.g. 9, 10] or solid contact ion‐selective electrodes 1122.…”
Section: Introductionmentioning
confidence: 99%
“…Reproduced with permission. [219] Copyright 2015, IEEE. h) Schematic illustration of RuO x FET sensor, with the functionalized 4-CPBA glucose sensing layer.…”
Section: F-fet Sensors Toward Health Monitoringmentioning
confidence: 99%
“…[11,160,[208][209][210] F-FET-based biochemical sensors could provide in situ monitoring of the sweat compositions in a noninvasive way. [211] Considering the complexity of sweat compositions, numerous sensors have been reported toward different ingredients, including pH sensors, [47,147,210,[212][213][214][215][216][217] ion sensors, [47,147,[218][219][220][221][222][223] glucose sensors, [21,45,48,159,[224][225][226] lactate sensors, [227] etc. Based on WO 3 NP, Santos et al [212] reported a representative F-FET-based pH sensor for in vivo applications (Figure 12e).…”
Section: F-fet Sensors Toward Health Monitoringmentioning
confidence: 99%